1999
DOI: 10.1016/s0378-1097(99)00438-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of type I pili is abolished in verotoxin-producing Escherichia coli O157

Abstract: Verotoxin-producing Escherichia coli (VTEC) were examined for production of type I pili. None of 34 strains of VTEC serogroup O157 examined expressed any pili, whereas 26 strains of 27 VTEC serogroup O26 and seven strains of nine non-VTEC O157 produced type I pili. These VTEC strains were collected from sporadic human cases and cattle in Okinawa in 1997. The genes encoding the major structural component (FimA) and the adhesin (FimH) of type I pili were detected in all 70 strains examined. The inability to expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
10
1
Order By: Relevance
“…Type I fimbriae may play a role in trauma-induced adherence of commensal E. coli to the murine cecum (19). However, modulation of type I fimbriae expression by NE could not explain the increased adherence of E. coli O157:H7 to the bovine ileal mucosa observed in this study, since E. coli O157:H7 strains contain a 16-bp deletion in the promoter region for the major fimbrial subunit and, as such, do not express type I fimbriae (12,37).…”
Section: Vol 72 2004contrasting
confidence: 56%
“…Type I fimbriae may play a role in trauma-induced adherence of commensal E. coli to the murine cecum (19). However, modulation of type I fimbriae expression by NE could not explain the increased adherence of E. coli O157:H7 to the bovine ileal mucosa observed in this study, since E. coli O157:H7 strains contain a 16-bp deletion in the promoter region for the major fimbrial subunit and, as such, do not express type I fimbriae (12,37).…”
Section: Vol 72 2004contrasting
confidence: 56%
“…Two previous studies indicated that expression of multiple horizontally acquired genes, scattered throughout the E. coli chromosome, is controlled by Ler and H-NS, and several of those genes encode proteins predicted to be associated with adhesion and/or agglutination (1,23). Although the identity of the novel hemagglutinin(s) expressed by the TMS002 (hns lpfA) and TMS003 (hns ler lpfA) mutant strains is currently unknown, our data suggest that in the absence of LPF, the E. coli O157:H7 strain is capable of (8,13,26). The idea of expression of other adhesins is supported by our in vivo studies, where the absence of the lpf genes causes a different pattern of colonization in animal models of infection (14,41), or in our ex vivo studies, where the mutant strain displayed a different tissue tropism in human intestinal biopsies (10).…”
Section: Discussionmentioning
confidence: 84%
“…coli O157:H7 strains carry the fimA genes for the type 1 fimbrial subunit but do not appear to be able to express fimA (14). A 16-bp deletion in the fim switch locks the expression phase in the "off" orientation only in VTEC O157 (45).…”
Section: Discussionmentioning
confidence: 99%